All roads are good native voices on life and culture. (Smithsonian Institution Press in association with the National Museum of the American Indian, Smithsonian Institution, 1994)
Objects from the collection of the National Museum of the American Indian, chosen by 23 Native Americans who also reflect on their cultural heritage.